The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1097/ccm.0b013e31822f0af5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a national propofol shortage on duration of mechanical ventilation at an academic medical center*

Abstract: An 84% decrease in propofol use in the adult intensive care units at our academic institution as a result of a national shortage did not affect duration of mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“…6 Adverse effects of drug shortages in oncology, 7,8 psychiatry, 9 and infectious disease 10,11 have been reported, but there is a paucity of data reflecting the effects of drug shortages on the practice of anesthesia or critical care. 4,5,12 In a 2011 survey conducted by the American Hospital Association, 95% of respondents indicated that drugs for anesthesia and surgery were in short supply. 13 Another survey conducted by the American Society of Anesthesiologists (ASA) revealed that drug shortages in anesthesia were associated with adverse patient outcomes, including death.…”
Section: Résumémentioning
confidence: 99%
“…6 Adverse effects of drug shortages in oncology, 7,8 psychiatry, 9 and infectious disease 10,11 have been reported, but there is a paucity of data reflecting the effects of drug shortages on the practice of anesthesia or critical care. 4,5,12 In a 2011 survey conducted by the American Hospital Association, 95% of respondents indicated that drugs for anesthesia and surgery were in short supply. 13 Another survey conducted by the American Society of Anesthesiologists (ASA) revealed that drug shortages in anesthesia were associated with adverse patient outcomes, including death.…”
Section: Résumémentioning
confidence: 99%
“…Realizing that the ECMO tubing and the membrane oxygenator of the ECMO circuit increase the drug volume of distribution and provide a large surface area for drug adsorption, further research is needed to evaluate the effect of the ECMO circuit on sedative pharmacokinetics and sedative response . Future ECMO sedative investigations will need to consider the complex distribution of sedatives between different body compartments, the various genomic and dynamic factors that affect sedative removal and clearance, and the numerous factors that will affect sedative response and patient outcome …”
Section: Discussionmentioning
confidence: 99%
“…The maximum amount of sedation administered in any 6‐hour period was therefore deemed, for the purposes of the study, to reflect the time during each patient's ICU stay during which sedative therapy first reached the desired therapeutic sedation goal and served as the primary outcome for the investigation. This 6‐hour window was based on the expected high frequency of benzodiazepine infusion use in the study population and has been used to characterize periods of ICU sedative exposure in other studies . Other important sedation‐related secondary outcomes compared between the two groups included the time to reach the maximum amount of sedation administered, the total cumulative amount of sedation administered to reach this maximum, and the total cumulative amount of sedation administered during the defined period of data collection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, audits will be immediately initiated to monitor the consequences of shortages as they occur. As an example of good practice, intensivists in Boston were able to show that restricted use of propofol sedation during a period of shortage did not adversely effect patient outcome [23].…”
Section: What Can Anaesthetists Do Now?mentioning
confidence: 99%